Effect of electroacupuncture on postoperative cognitive dysfunction for patients undergoing total knee arthroplasty: A protocol for systematic review and meta-analysis of randomized controlled trials. Issue 4 (29th January 2021) - Ye, Zixuan; Ke, Mingjing; Wang, Tao; Guan, Yingxin; Ou, Liang; Zheng, Linbiao; Chen, Zehua; Shen, Zhen; Zheng, Liuyi; Yuan, Changfei; Li, Wenyao; Liu, Jinqing; et al.
Abstract: Background: Electroacupuncture is increasingly used in rehabilitation for postoperative cognitive dysfunction (POCD), but relevant evidence remains unclear for patients receiving total knee arthroplasty (TKA). Methods: The databases research of PubMed, EMBASE, CINAHL, and China National Knowledge Infrastructure (CNKI) will be conducted from inception to December 31, 2020. The relevant randomized controlled trials (RCTs) from data will be screened one by one. The remaining studies that meet the inclusion criteria will be extracted and analyzed using RevMan V.5.3 software. Paired 2 reviewers will assess quality of the included studies and publication bias by using the Cochrane Collaboration risk of bias tool, and Egger test and Begg test respectively. And grading of recommendations assessment, development and evaluation (GRADE) will be used to estimate the quality of evidence. Results: In this study, we will analyze the effect of electroacupuncture on Mini-Mental State Examination (MMSE), interleukin 1β (IL-1β), tumor necrosis factor-α (TNF-α), S100-β protein, and adverse events for patients with TKA. Conclusion: Our findings will provide evidence for the effectiveness of electroacupuncture on the treatment and prevention of POCD for TKA patients. Registration number: Available at: https://osf.io/azyt9 (DOI number: 10.17605/OSF.IO/AZYT9).